Ekstrakurikuler Gitar Akustik Di SMAN 1 Kota Sungai Penuh - Roman Jomes; Tulus Handra Kadir (FBS Universitas Negeri Padang, 2021)
This study aims to describe the implementation of acoustic guitar extracurricular. This research belongsto a descriptive research using a qualitative approach. The data were collected through observation, interview, and documentation. The Data analysis started from data collection stage, reduction stage, data presentation stage, and the conclusion stage. Data validity testwasconducted by extending observations and increasing persistence.The results of this study indicate that: (1) extracurricular planning includes: a. the material taught is carried out in steps, b. The method used is the lecture method, demonstration method, question and answer method, and assignment method, (2) extracurricular implementation includes: initial activities, core activities, and final activities, (3) learning evaluation includes evaluation of the process seen from the discipline, activeness, and motivationof the students. Thelearning outcome evaluationis conductedby using indicators of technique, material, and appearanceon students’ demonstration. Based on the results of this study, it can be suggested that the school continues to maintain music extracurricularso that students can continue to develop in music. Through the extracurricular of music, especially in acoustic guitar extracurricular, it is hoped that it can accommodate students who want to develop talents in the music field.